Understanding Islamic Economic Principles and Their Relevance to Challenges in the Digital Age - Nur Majdina (International Research of Economic and Management Education, 2022)
The times have given rise to various innovations, technology and digitization. These changes are of course closely related to the economic and social activities of the community, therefore it is important to understand how the principles of Islamic economics lay the foundations of economic policies that are developed based on the instructions of the Qur'an and Sunnah in facing various challenges in the digital era of globalization. Through a study with a qualitative approach, this study aims to describe the relevance of policies in the Islamic economy to changes in economic activity in the digital era. The method used in this research is library research or literature review, which collects data from the literature and other sources that support and are related to the discussion in this study. The results of the discussion in this study: 1) The relevance of the digital era is very clear in relation to changes in economic cases including information transactions, finance transactions and goods transactions. 2) Economic transactions with their various changes in the digital era, do not conflict with Islamic economic principles as long as they are in accordance with the validity of a contract, and meet the requirements and applicable laws. This research is limited to a qualitative approach through literature review which can be redeveloped with another approach using data analysis methods in case studies, considering the many contemporary economic cases that can be used as research material. This study illustrates the important role of a proposition through Islamic economic principles, where a limited argument can answer unlimited contemporary economic cases.